Detection and identification of Lactobacillus bacteria found in the honey stomach of the giant honeybee Apis dorsata. - Tajabadi, Naser; Mardan, Makhdzir; Abd. Manap, Mohd. Yazid; Mustafa, Shuhaimi; Meimandipour, Amir; Nateghi, Leila (Springer Verlag, 2011)
This is the first assay that describes the isolation and identification of strains and species of Lactobacillus from the honey stomach of the Asiatic giant honeybee, Apis dorsata. Samples of honeybees were collected from A. dorsata colonies in different bee trees, and Lactobacillus was isolated from honey stomachs using selective media. The isolates were Gram-stained and tested for catalase reaction. The 16S rRNA genes from extracted DNA of bacterial colonies were amplified with polymerase chain reaction using lactobacilli genus primers (27F and 1492R). All bacterial 16S rRNA genes were sequenced and deposited in GenBank. The 34 isolated strains yielded three distinct rRNA sequences of 15 different strains. Lactobacillus sequences isolated from the bees' honey stomachs were comprised of Lactobacillus kunkeei related-sequences (56%) with other abundant sequences being related to other Lactobacillus sp. (38%) and Lactobacillus vermiform (6%). These strains can be good candidates for potential application as probiotics in honeybees and also as natural food preservatives, which, in turn, may be useful in the food industry.